Why we buy; shopping and the purchasing environment - Mitchell, Vincent-Wayne (Henry Stewart Talks, 2015)
Physical commerce environment, Physical commerce: locating mindset, Physical commerce: exploring mindset, Physical commerce: dreaming mindset, E commerce, M commerce, F commerce